Neuroimaging Study Investigating the Supraspinal Control of Lower Urinary Tract Function in Man With Orthotopic Ileal Neobladder - Wu, Wanhua; Su, Yun; Huang, Hao; Chen, Meiwei; Fan, Fan; Zhu, Dingjun; Li, Kaiwen; Guo, Zhenghui; Liang, Zhiying; Huang, Hai (Frontiers in Surgery, 2021)
Introduction: Recent studies employing functional imaging methodology have revealed reference brain regions of urinary tract function, namely, the midbrain periaqueductal gray matter, thalamus, and cingulate and prefrontal cortices. The orthotopic ileal neobladder is a desirable method for urinary diversion after radical cystectomy, but its supraspinal control remains unknown. We aimed to evaluate brain activity while maintaining urinary urgency and voluntary urinary control in male subjects with ileal orthotopic neobladders by performing functional MRI (fMRI) during a block design experiment. Materials and Methods: Patients were recruited at the Sun Yat-sen Memorial Hospital of the Sun Yat-sen University from October 2017 to May 2019. Two tasks were performed during fMRI scanning: (1) repeated infusion and withdrawal of sterile saline solution into and out of the neobladder to simulate urgency; and (2) repeated contraction of the pelvic floor muscle with a full neobladder to induce inhibition of micturition since the subjects were asked not to urinate. The obtained data were visualized and statistically analyzed. Results: Sixteen subjects were recruited in the study, and data were obtained from 10 subjects: mean age 60.1 years, average postoperative time 20.2 months, and daytime continence rate 100%. The parahippocampus, frontal lobe, vermis, and anterior cingulate cortex were activated with large bladder volumes, and the thalamus and caudate nucleus were deactivated during voluntary urinary control. Conclusion: A complex supraspinal program is involved during ileal orthotopic neobladder control, which is significantly different from that with normal bladders, in which the original intestine visceral volume sensation is preserved.